Pastoralism beyond the past - Leneman, J.M.; Reid, Robin S. (2001)
This paper focuses on the changes affecting the world's pastoral systems in the context of globalization, and considers whether pastoralism will survive modern times. Opportunities for pastoral livelihood improvement are explored.